Endoscopic Orbital Decompression for Graves’ Ophthalmopathy - Tang, Ing Ping; Prepageran, Narayanan; Shashinder, S. (Malaysian Medical Association, 2008)
We report a male patient of Graves’ Disease with bilateral exophthalmos who had undergone bilateral transnasal endoscopic orbital decompression with subsequent improvement of 3mm in orbital proptosis bilaterally without any complications. Transnasal endoscopic orbital decompression is recommended as an alternative to traditional decompression techniques especially for purely cosmetic reasons.